Genetic polymorphisms of 17 Y-STR loci in Eastern Turkey population - Tokdemir, Mehmet; Tuncez, Ferhat Turgut (Elsevier Science Bv, 2017)
The allele frequencies and haplotypes for the 17 Y-STR (Y-chromosomal short tandem repeat) loci (DYS456, DYS389I, DYS390, DYS389II, DYS458, DYS19, DYS385a/b, DYS393, DYS391, DYS439, DYS635, DYS392, Y GATA H4, DYS437, DYS438 and DYS448) are determined in a sample of 457 unrelated male individuals living in Eastern Anatolia Region in Turkey using the AmpFlSTR (R) YfilerTM PCR Amplification Kit. In this studywe find 427 different haplotypes that the observed haplotype diversity (HD) is 0.9986 and discrimination capacity (DC) is 0.9343. The calculated average gene diversity (GD) varies between 0.445 (DYS391) and 0.954 (DYS385a/b). Genetic distance comparisons of the Eastern Turkey Y-STR database are calculated with those from the nearby countries (Iran, Iraq, Azerbaijan, Turkish Cypriots, Greece) and relatively distant countries (Romania, Italy, Germany, Spain, South Africa, China, Brazil, Australia) through the use of analysis of molecular variance (AMOVA) and multidimensional scaling (MDS). (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Y-STR; Y-filer; Eastern Turkey population